2011
DOI: 10.1634/theoncologist.2010-0222
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Induces Rapid Plasma Glucose Normalization in Insulinoma Patients by Effects on Tumor As Well As Normal Tissues

Abstract: Methods. Three consecutive patients with a metastasized symptomatic insulinoma were started on 100 g of octreotide subcutaneously three times daily. Because of persisting hypoglycemias, treatment with daily 10 mg of oral everolimus was initiated. Serial plasma glucose levels and serum insulin levels were measured. Computer tomography (CT) scans were performed before and after 2 and 5 months of treatment.[18F]fluoro-2-deoxy-d-glucose positron emission tomography (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 22 publications
3
53
0
1
Order By: Relevance
“…Data on everolimus in the control of hypoglycemic symptoms have been recently published (20,21,22,23). Our study confirms these data, with the largest number of patients ever reported in the literature and a significant duration of follow-up.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Data on everolimus in the control of hypoglycemic symptoms have been recently published (20,21,22,23). Our study confirms these data, with the largest number of patients ever reported in the literature and a significant duration of follow-up.…”
Section: Discussionsupporting
confidence: 88%
“…In two of four patients, partial responses were observed at 16 and 29 months. Four other case reports mentioned successful efficacy of mTOR inhibitors in controlling hypoglycemia (11,21,22,23), although failure to control hypoglycemic symptoms was reported in one case (24).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 8 retrospective studies were identified (Bernard et al 2013;Capdevila et al 2015;Ferrer-Garcia et al 2013;Fiebrich et al 2011;Kulke et al 2009;Liu et al 2016;Panzuto et al 2014;Tippeswamy et al 2015), which included a total of 183 patients with pancreatic and 135 patients with extra-pancreatic NETs (see Table 2a). …”
Section: Published Retrospective Studiesmentioning
confidence: 99%
“…Most patients were treated with everolimus as a second line drug, after failure of the previous medical treatments. Taking into account this limitation, treatment with everolimus led to disease stabilization in more than half of patients (Liu et al 2016;Tippeswamy et al 2015), and disappearance of hypoglycaemic symptoms in malignant insulinomas (Fiebrich et al 2011).…”
Section: Published Retrospective Studiesmentioning
confidence: 99%
“…Pancreatic surgery reduces the amount of functional parenchyma, streptozotocin is cytotoxic to pancreatic b-cells, octreotide and everolimus reduce insulin secretion, and everolimus also increases insulin resistance (5,6). A potential consequence of these therapies is the onset of prediabetes or diabetes mellitus, which is commonly associated with increased long-term, all-cause mortality in oncologic patients (7).…”
mentioning
confidence: 99%